2018
DOI: 10.15184/aqy.2017.196
|View full text |Cite
|
Sign up to set email alerts
|

The Viking Great Army in England: new dates from the Repton charnel

Abstract: Repton

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 29 publications
1
35
0
Order By: Relevance
“…For instance, the bones recovered from Repton (England) were associated with the Viking Great Army from 873- 20 874 CE based on the archaeological context, however early radiocarbon results predated some of them to the seventh and eighth centuries CE (12). Only a later radiocarbon analysis that considered the marine reservoir effects found that all dated remains are consistent with a single late ninthcentury event, in line with the numismatic evidence (13).…”
mentioning
confidence: 60%
See 1 more Smart Citation
“…For instance, the bones recovered from Repton (England) were associated with the Viking Great Army from 873- 20 874 CE based on the archaeological context, however early radiocarbon results predated some of them to the seventh and eighth centuries CE (12). Only a later radiocarbon analysis that considered the marine reservoir effects found that all dated remains are consistent with a single late ninthcentury event, in line with the numismatic evidence (13).…”
mentioning
confidence: 60%
“…Dating the13 Brandysek individuals, Czechia. Two individuals from (RISE568 and RISE569) the Brandysek site, were originally attributed by archaeological context to the Bell Beaker period (4,800-3,800 BP)(17).…”
mentioning
confidence: 99%
“…Longstanding dispute was raised by radiocarbon dates, which appeared to indicate a long period of use beginning before the Viking Age. New analysis has finally clarified the issue thanks to a full study of the isotopic signal, which revealed that the initial results had failed to consider the marine reservoir effect caused by a fish-rich diet (Jarman et al 2018). Once recalibrated, the dates are consistent with the Great Army activities.…”
Section: A Scientific Approach To Mobilitymentioning
confidence: 99%
“…The Roman population of York also contained several mobile individuals and a small peak shows one mobile individual dating to the ninth century of probable Scandinavian origins. (Biddle & Kjølbye-Biddle 2001;Budd et al 2004;Jarman et al 2018). We also estimated, using a combination of 87 Sr/ 86 Sr and/or δ 18 O measurements, the place of origin of a young individual (SK27), buried in a high medieval leprosarium in Winchester, UK with a scallop shell typical of a pilgrim who completed the travel to Santiago de Compostela.…”
Section: Bayesian Modellingmentioning
confidence: 99%